Relatos de experiências nas aulas de matemática na modalidade remota em algumas escolas privadas de educação básica - Marques, Renata de Fatima (2022)
Mathematics teaching has always been labeled due to the stigma of being a "difficult subject", with this, there are many teaching methodologies which can be applied to attract the attention of students. However, due to the COVID-19 pandemic established in 2020, teachers abruptly had to adapt to their mote teaching model, having to innovate their way of teaching. The objective of this work is to seek information about the performance of the mathematics teacher in 2020, through research that will be done using GoogleForm. This is justified, because we believe that it is through experiences that we find paths that lead us to reflect on the formation of the individual. We consider that the pandemic-imposed changes in teaching practice and that the use of digital technologies became necessary for remote teaching, in order to be the means of dialogue between educator and student.